Enhanced Ion Conductivity in Conducting Polymer Binder for High‐Performance Silicon Anodes in Advanced Lithium‐Ion Batteries. Issue 11 (8th January 2018) - Zeng, Wenwu; Wang, Lei; Peng, Xiang; Liu, Tiefeng; Jiang, Youyu; Qin, Fei; Hu, Lin; Chu, Paul K.; Huo, Kaifu; Zhou, Yinhua
Abstract: Polymer binders with high ion and electron conductivities are prepared by assembling ionic polymers (polyethylene oxide and polyethylenimine) onto the electrically conducting polymer poly(3, 4‐ethylenedioxythiophene): poly(styrenesulfonate) chains. Crosslinking, chemical reductions, and electrostatics increase the modulus of the binders and maintain the integrity of the anode. The polymer binder shows lithium‐ion diffusivity and electron conductivity that are 14 and 90 times higher than those of the widely used carboxymethyl cellulose (with acetylene black) binder, respectively. The silicon anode with the polymer binder has a high reversible capacity of over 2000 mA h g −1 after 500 cycles at a current density of 1.0 A g −1 and maintains a superior capacity of 1500 mA h g −1 at a high current density of 8.0 A g −1 . Abstract : A novel polymer binder with high ion and electron conductivities that are 14 and 90 times higher than those of the widely used carboxymethyl cellulose (with acetylene black) binder, respectively, is achieved. Crosslinking, chemical reductions, and electrostatics increase the modulus of the binders and maintain the integrity of the anode that contributes to the enhanced electrochemical performance.